Impact of Environmental Pollution in Coastal Areas: A Review - Ramadhan Tosepu; Sitti Umu Nasibah; Sariyanti (Journal of Health Science and Pharmacy, 2025)
Background: Coastal areas are particularly vulnerable to environmental pollution due to both anthropogenic activities and natural processes. Pollution in these regions includes water contamination, industrial discharges, plastic waste accumulation, and eutrophication, all of which contribute to the degradation of marine ecosystems. Objective: This study aims to analyze the causes, impacts, and potential solutions to environmental pollution in coastal areas through a comprehensive literature review of previous research studies. Method: The study employed a literature analysis approach, drawing from a wide range of scientific publications and sources that examine various aspects of coastal pollution. Results: The review indicates that pollution in coastal areas poses significant risks to human health, contributes to the deterioration of marine ecosystem quality, and threatens the sustainability of fisheries and tourism industries. Key contributing factors include the unregulated discharge of industrial and domestic waste, high volumes of plastic waste, and nutrient runoff from agricultural activities leading to eutrophication. Conclusion: Effectively addressing coastal pollution requires a multidisciplinary strategy involving government regulation, advancements in waste treatment technologies, and active community engagement. The implementation of community-based policies and the strengthening of coastal conservation programs are essential measures for mitigating environmental degradation. Keywords: Environmental Pollution, Coastal Areas, Waste, Marine Ecosystems, Mitigation.